NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL SI ANAK PELANGI KARYA TERE LIYE DAN RELEVANSINYA DENGAN PEMBELAJARAN TEMATIK DI MI - Arifin, Nadia Nurul; Mangkuwibawa, Hilman; Muhamadi, Sani Insan (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2023)
This study aims to describe the values contained in the novel Si Anak Pelangi by Tere Liye and its relevance to thematic learning at MI. The method used in this study is a descriptive analysis method with a qualitative approach. This aims to obtain the results of the analysis and description of the educational values of the characters in the novel Si Anak Pelangi by Tere Liye. The data analysis used is miles and huberman model analysis with stages of data reduction, data presentation and drawing conclusions. The value of education in the novel Si Anak Pelangi by Tere Liye contains 18 values of character education based on the Ministry of Education and Culture. Meanwhile, the relevance of this novel to thematic learning in grade 5 MI contains six, namely religious values, honesty, tolerance, love of the homeland, peace-loving, and responsible. Keywords: Character Building, Novel Literature, Thematic Learning